A 68 years Old Man with Compressive Chest Pain and Breathlessness - Cader, F Aaysha; Haq, M Maksumul; Ghafoor, Nusrat (Journal of Bangladesh College of Physicians and Surgeons, 2016)
Abstract not available J Bangladesh Coll Phys Surg 2015; 33(4): 232-234